Ostracods from the Kunming area of SW China, with description of two new species and male records of Cypridopsis vidua (O.F. Müller, 1776) - Zhai, Dayou; Fan, Jiawei; Wang, Min (Zootaxa, 2023)
Previous studies of the Recent non-marine ostracods of Yunnan Province in southwestern China yielded 42 species, among which only 18 species were reported based on living material. Such a low number is likely to underestimate the species diversity of ostracods in Yunnan, considering the geographical disparity among its different parts. In this study, we report 11 nominal species and one species left in open nomenclature from 22 samples collected from the Kunming area in eastern-central part of Yunnan. Among these species, seven are new to the province, including Notodromas semiovata n. sp., Chrissia acuminata n. sp., and the first records of the male of Cypridopsis vidua (O.F. Müller, 1776) outside the USA. A review of previous literature indicates that, with the exception of the two new species, all the other 23 species have Palaearctic (PA) distributions, while only 14 have Oriental (OL) distributions. Such a composition contradicts previous vertebrate-based zoogeographical subdivisions of China in which Yunnan was included in the OL region, and adds to the argument that the geographical distributions of various invertebrate groups need to be investigated to map the PA‒OL boundary in China more appropriately.